Avaliando o Forecast content dos modelos auto-regressivos para a arrecadação de ICMS do setor elétrico no Estado do Ceará - Moraes, Francisco Ozanan Bezerra de (2011)
In this essay we investigate the loss of content in autoregressive forecast models, as it is increased the horizon of time in which the variable is estimated. The content is measured as the proportionate reduction in medium squared error (MSE) that the model gives, comparing to the simple process by using the unconditional mean of time series. The variable is the monthly collection of ICMS from electric power sector, in Ceará state, in the period from January 1999 to September 2010. We use the method and computational model formulated by Galbraith (2003), analyzing the forecast content function, in which the content depends on the number of estimated periods. The results confirm that, when it increases the range of forecast the content decays quickly, reaching less than 10% when the forecast horizons reaches 5 months. It was found further that the use of subsamples by discarding oldest periods increases the loss of content.